Biochemical Diagnostic Significance of Cannabis Indica Misuse in Society- A Socio-Behavioral Validation Study - Langah, Ishtiaque Ali; Zaman, Nayyer IZ; ullah, Habib; Anwar, Zahida; Ullah, Ikram; Asad, Muhammad; Khan, Jamshed (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Cannabis indica, usually known as weed, has transitioned from a traditional herb to a widely misused psychoactive substance. While its medicinal value is acknowledged, its misuse especially among youth has become a silent epidemic. The normalization of recreational use, increased potency, and early exposure have contributed to a rise in cannabis use disorder (CUD), cognitive decline, and social dysfunction. Objective: To determine the diagnostic significance of Cannabis indica misuse in society using behavioral screening tools as the gold standard. Study Design: Cross-sectional validation study. Material and Methods: A cross-sectional validation study was conducted on 140 individuals aged 15–45 years in urban centers of Kashmir from 01-01-2025 to 01-07-2025. Participants were screened for cannabis misuse using self-reported frequency, DSM-5 criteria, and the Cannabis Use Disorder Identification Test-Revised (CUDIT-R). Behavioral assessments were used as the gold standard. Results: Among 140 participants, 94 (67.1%) were under 30 years of age. 46 (32.9%) were over 30. 48 individuals (34.3%) met criteria for cannabis misuse, while 92 (65.7%) did not. Of these, 36 were true positives, 12 false positives, 80 true negatives, and 12 false negatives. The sensitivity of self-reported cannabis misuse was 75.0%, specificity 86.9%, positive predictive value 75.0%, and negative predictive value 86.9%. Conclusion: Cannabis misuse is underreported and often masked by cultural normalization. While self-reporting shows moderate sensitivity, behavioral screening tools offer higher diagnostic reliability. Early detection and intervention are essential to mitigate long-term harm.